Development of Character-Based Islamic Religious Education Learning Technology - Rohanita, Lailatur; Acetylena, Sita (PT. Riset Press International, 2025)
This study aims to describe the development of character-based Islamic Religious Education (PAI) learning technology at MTs NU Miftahul Huda Turen. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation. The results show that MTs NU Miftahul Huda has a strong commitment to building students' Islamic character through the integration of Ahlussunnah wal Jama'ah Islamic values into the learning process, both curricularly and culturally. Learning strategies are developed through a combination of the national curriculum and NU-an, habituation of religious activities, teacher role models, and extracurricular activities that support values such as discipline, responsibility, and tolerance. Challenges faced include limited human resources and infrastructure, especially in the use of learning technology. Nevertheless, this madrasah is able to demonstrate positive transformation, seen in the improvement of students' spiritual character and academic and non-academic achievements. This study recommends strengthening teacher capacity and developing technological infrastructure to support character learning that is adaptive to changing times.